2011
DOI: 10.1159/000321894
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of a Well-Structured Diagnostic Process in Colon Cancer

Abstract: Introduction: Preoperative work-up in colorectal cancer is comprehensive and can be time consuming. In our institution, the preoperative track for colorectal patients was reorganized in order to reduce the therapeutic delay and the number of outpatient clinic visits. We assessed the impact upon the patient outcomes. Methods: All consecutive patients with colon cancer who entered the reorganized preoperative track between January 2008 and December 2009 (n = 87) were retrospectively compared with a consecutively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Studies indicate that the strategy can be both effective and efficient. A Dutch study of direct access to colonoscopy for abdominal symptoms showed reduced time to diagnosis and more efficient use of tests ( Klemann et al , 2011 ). This is supported by studies from the United Kingdom ( Maruthachalam et al , 2005 ; Ahmed et al , 2013 ).…”
Section: The Nycmentioning
confidence: 99%
“…Studies indicate that the strategy can be both effective and efficient. A Dutch study of direct access to colonoscopy for abdominal symptoms showed reduced time to diagnosis and more efficient use of tests ( Klemann et al , 2011 ). This is supported by studies from the United Kingdom ( Maruthachalam et al , 2005 ; Ahmed et al , 2013 ).…”
Section: The Nycmentioning
confidence: 99%
“…Direct access to imaging and endoscopy has been shown to improve care in a number of countries. For example, a Dutch study has demonstrated that direct access colonoscopy reduces diagnostic delay and specialist workload without markedly increasing the volume of procedures done [ 8 ]. A Danish study has shown that direct access to CT Thorax did not increase test use but significantly reduced specialist time per patient and with high staff acceptability [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…After this day patients are discussed in a multidisciplinary team. Afterwards a second outpatient clinic visit is planned with the colorectal surgeon to discuss the definitive plan of surgery [15]. Importance of such a fast and well-structured diagnostic process has been shown in several studies stating that a longer therapeutic delay causes more psychological distress in oncology patients [15e18].…”
Section: Discussionmentioning
confidence: 99%